Kajian Meningkatkan Kesediaan Kontraktor Terhadap Penggunaan Teknologi Artificial Inteligent (AI) dalam Amalan Keselamatan dan Kesihatan Pekerja (KKP) di Tapak Bina - Mahasan, Mohamad Amirullah; SHAFII, HARYATI; OMAR, ROSHARTINI; Sarpin, Norliana; kHALID, ZAILAWATI; Md Yassin, Azlina; Masram, Haidaliza (Research in Management of Technology and Business, 2024)
Recently, Artificial Intelligence (AI) has experienced rapid development and plays an important role in various industries, including construction. This study’s problem is worker safety and health, which has contributed to the increase in worker accidents at construction sites. The current safety and health management practices still have weaknesses. Therefore, this study aims to examine methods to enhance contractors’ readiness to use AI technology in safety and health management, investigate the challenges contractors face in adopting AI technology for safety and health practices, and suggest steps to improve contractors’ readiness to use AI technology. This study uses a qualitative method, namely interviews with G6 contractor respondents. The respondents consist of G6 contractors who have construction projects in Johor Bahru, Johor. The results of this study found that there are several aspects to improve contractors’ readiness to use AI technology for safety and health at construction sites. These include establishing industry collaborations, creating online platforms or forums, starting with small projects, and so on. In conclusion, it is hoped that the study on AI technology can contribute to the construction industry, especially in addressing safety and health issues at construction sites.